Leadership and Work-Related Attitude Among Bank Employees in Northern Region of Malaysia - Asaari, Muhammad Hasmi Abu Hassan; Desa, Nasina Mat; Ali, Mohamed Asri Mohd (MIJP Publication, 2017)
This paper explores the bank employees’ leadership that associated with their work-related attitude. Moreover, it also examines the impact of bank employees’ leadership on their work-related attitude. The population of this study is the bank employees in the Northern Region of Malaysia. These bank employees are the respondents that receive a self-administered questionnaire for them to answer pertaining to their leadership and work-related attitude. Leadership Behavior Development Questionnaire (LBDQ-XII) is used to measure leadership; and work-related attitude is using questions by previous researchs. With a positive work-related attitude, the bank could gain and retain good and industrious employees in their work-related attitude whom will help the bank to achieve its mission, vision, and goals; in one word - “profit”